Emergence of Pituitary Adenoma in a Child during Surveillance: Clinical Challenges and the Family Members’ View in an AIP Mutation-Positive Family - Pedro Marques; Sayka Barry; Amy Ronaldson; Arla Ogilvie; Helen L. Storr; Peter J. Goadsby; Michael Powell; Mary N. Dang; Harvinder S. Chahal; Jane Evanson; Ajith V. Kumar; Joan Grieve; et al. (International Journal of Endocrinology)
Introduction. Germline aryl hydrocarbon receptor-interacting protein (AIP) mutations are responsible for 15–30% of familial isolated pituitary adenomas (FIPAs). We report a FIPA kindred with a heterozygous deletion in AIP, aiming to highlight the indications and benefits of genetic screening, variability in clinical presentations, and management challenges in this setting. Patients. An 18-year-old male was diagnosed with a clinically nonfunctioning pituitary adenoma (NFPA). Two years later, his brother was diagnosed with a somatolactotrophinoma, and a small Rathke’s cleft cyst and a microadenoma were detected on screening in their 17-year-old sister. Following amenorrhoea, their maternal cousin was diagnosed with hyperprolactinaemia and two distinct pituitary microadenomas. A 12-year-old niece developed headache and her MRI showed a microadenoma, not seen on a pituitary MRI scan 3 years earlier. Discussion. Out of the 14 members harbouring germline AIP mutations in this kindred, 5 have pituitary adenoma. Affected members had different features and courses of disease. Bulky pituitary and not fully suppressed GH on OGTT can be challenging in the evaluation of females in teenage years. Multiple pituitary adenomas with different secretory profiles may arise in the pituitary of these patients. Small, stable NFPAs can be present in mutation carriers, similar to incidentalomas in the general population. Genetic screening and baseline review, with follow-up of younger subjects, are recommended in AIP mutation-positive families.